1) sin a = √2/2; a1 = pi/4+2pi*k; cos a1 = √2/2 a2 = 3pi/4+2pi*k; cos a2 = -√2/2 cos(60 + a1) = cos 60*cos a1 - sin 60*sin a1 = = 1/2*√2/2 - √3/2*√2/2 = √2/4*(1 - √3) = -√2(√3 - 1)/4 cos(60 + a2) = cos 60*cos a2 - sin 60*sin a2 = = -1/2*√2/2 - √3/2*√2/2 = -√2/4*(1 + √3) = -√2(√3 + 1)/4
2) sin a = 2/3; cos b = -3/4; a ∈ (pi/2; pi); b ∈ (pi; 3pi/2) cos a < 0; sin^2 a = 4/9; cos^2 a = 1-4/9 = 5/9; cos a = -√5/3 sin b < 0; cos^2 b = 9/16; sin^2 b = 1-9/16 = 7/16; sin b = -√7/4 sin(a+b) = sin a*cos b + cos a*sin b = = 2/3*(-3/4) + (-√5/3)(-√7/4) = -6/12 + √35/12 = (√35 - 6)/12 cos(-b) = cos b = -3/4
-3х+у=1
1)у = 1 +3 х
15х - 4(1 +3 х) = 8
15х - 4 - 12 х = 8
3 х = 12
х = 4
2)у = 1 +3 х
у = 1 + 3*4 = 13
ответ:(4;13)
второе :
Х+у=45
Х-у=13
2х = 58
х=29
2)Х-у=13
29 - у = 13
- у = 13 - 29
- у = - 16
у = 16